The Role of 3D-pCASL MRI in the Differential Diagnosis of Glioblastoma and Brain Metastases - Solozhentseva, Kristina; Batalov, Artem; Zakharova, Natalia; Goryaynov, Sergey; Pogosbekyan, Eduard; Pronin, Igor (Frontiers in Oncology, 2022)
Purpose The first aim of this study was to compare the intratumoral and peritumoral blood flow parameters in glioblastomas and brain metastases measured by pseudocontinuous arterial spin labeling MRI (3D pCASL). The second aim of this study was to determine whether pCASL could aid in identifying the source of brain metastases. Materials and Methods This study included 173 patients aged 12 to 83 years (median age—61 years), who were observed at the National Medical Research Center for Neurosurgery. All patients underwent preoperative MRI with pCASL perfusion. Thereafter patients were operated on and received histological diagnosis. No patients received preoperative chemo or radiotherapy. Results The values of maximum and normalized intratumoral blood flow were significantly higher in the group with gliblastoma than in the group with brain metastases: 168.98 + −91.96 versus 152.1 + −173.32 and 7.6 + −8.4 versus 9.3 + −5.33 respectively (p <0.01). However, ROC analysis showed low AUC specificity and sensitivity (0.64, 70%, 60% for mTBF and 0.66, 77%, 62% for nTBF). Peritumoral blood flow parameters were also higher in the glioblastoma group (29.61 + −22.89 versus 16.58 + −6.46 for mTBF and 1.63 + −1.14 versus 0.88 + −0.38 for nTBF, respectively; p <0.01). ROC analysis showed the following measurements of AUC, specificity, and sensitivity (0.75, 68%, 73% for mTBF and 0.77, 58%, 91% for nTBF). Regarding pCASL and various histological subsets of brain metastases, the study found statistically significant differences between the lung and melanoma metastases and the lung and kidney metastases. ROC analysis gave the following values for lung and melanoma metastases: AUC—0.76, specificity—75%, and sensitivity—73% for mTBF; 0.83, 67%, and 93% respectively, for nTBF. For lung and kidney metastases: AUC—0.74, specificity—70%, and sensitivity—93% for mTBF; 0.75, 70%, and 93% respectively, for nTBF. Conclusions pCASL could aid in differential diagnosis between glioblastoma and brain metastases. Measurement of peritumoral blood flow demonstrates higher specificity and sensitivity than with intratumoral blood flow. Moreover, pCASL provides the ability to distinguish lung metastases from kidney and melanoma metastases.